A Mixed Methods Study to Examine the Influence of CLIL on Physical Education Lessons: Analysis of Social Interactions and Physical Activity Levels - Salvador-García, Celina; Capella-Peris, Carlos; Chiva-Bartoll, Oscar; Ruiz-Montero, Pedro Jesús (Frontiers in Psychology, 2020)
Physical education is often selected for applying multilingual initiatives through the use of the content and language integrated learning (CLIL) approach. However, it is still unclear whether the introduction of such approach might entail losing Physical Education’s essence and distorting its basic purposes. The aim of this study is to analyse the impact of CLIL on the Physical Education lessons. Given the purpose of this study, a mixed methodological approach based on a sequential exploratory design divided in two different phases is used. We begin with an initial qualitative data collection (phase I) consisting in the analysis of interviews with 12 participants (8 teachers and 4 students). Based on its analysis, two foci are identified: social relationships and physical activity. Then, informed by the results obtained, a quantitative approach is used (phase II), differentiating these two sets of data to deepen on them. On one part, a sociometric questionnaire was applied to analyse the social relationships among CLIL students. On the other part, a quasi-experimental design (n = 49) was implemented using accelerometry to measure the MVPA of the PE sessions. Regarding physical activity, the results show that levels of MVPA are higher in the experimental group (CLIL) than in the control group showing light to the divergent viewpoints of interviewees. However, focusing on social relationships, the sociometric questionnaire results show that there were no statistical significative changes, although some signs of a slight effect on students’ relationships arise depending on their gender. Therefore, more research would be necessary to deepen on how CLIL affects in this regard.